Investigation of Heat Pump Drying for Herbal Passion Flower (Passiflora Foetida) Tea Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Passion flower (Passiflora foetida) is indigenous to many parts of Vietnam. Passion flower is a highly valued calmative nerve, used for nervous relentlessness, as a gentle sedative for sleep difficulties, and to reduce anxiety, neurasthenia, and nervous disorders. Passion flower is generally considered to be a safe herb, well tolerated and side effects are rare. Biologically active constituents include flavonoids, maltol, and indole alkaloids alkaloids, among numerous other constituents.  In order to utilize this good source as a healthy herb, we attempted to produce dried passion flower herbal tea. Heat pump technology has been used for heating, ventilation, and air-conditioning in fruit and vegetable industry. The main objective of heat pump drying is to produce a dried passion flower tea of desired quality at minimum cost and maximum throughput and to optimise these factors consistently. We focused on investigation of blanching, drying and storage of dried passion flower tea. Results showed that blanching at 95 oC in 10 seconds, drying by heat pump at 20 oC, vacuuming and packing in PET/AL/PE bag could maintain the flavonoid content in the dried passion flower tea.Keywords: Passion flower, Passiflora foetida, Heat pump drying, Herbal tea, Vacuuming, Blanching.